Indonesian and Korean teachers’ awareness of interculturality and world Englishes - Lestiono, Riski; Setyaningrum, Rina Wahyu; Gusdian, Rosalin I.; Rifah, Lailatul (Journal of Education and Learning (EduLearn), 2024)
English for young learners (EYL) teachers have practiced some creative activities to maintain their pupils’ learning with natural exposure to the target language amidst the pandemic. One activity practiced by Indonesian and Korean teachers was an international collaboration to perform a virtual drama of each country’s folktale. This phenomenological research aimed at tapping the teachers’ perceptions regarding interculturality and world Englishes (WE) in the virtual dramatic play collaboratively conducted and delving into their commitments in honing interculturality and WE. Two Indonesian and Korean teachers were involved in three sessions of in-depth interviews using pre-prepared interview questions. The trustworthiness of the data was achieved by the group discussions allowing the participants to comment on and revise the transcribed data, as well as triangulation by two international collaborators. Thematic analysis was performed to identify emerging themes and to provide novel insights into EYL teachers' encounters with interculturality and WE. The Indonesian and Korean teachers admitted the compatibility between language and culture, the urgency of introducing varieties of English, and the merits of conducting international collaboration to promote interculturality and WE. The teachers are committed to integrate interculturality and WE in their instructions despite some differences in the stipulated curricula.